Resilient spatial transformation and governance of public spaces in historical districts in disaster time: a literature review - Zijia Li; Chenhao Wang; Jiwu Wang (Journal of Asian Architecture and Building Engineering)
Modern disaster prevention facilities cannot play an effective role in China’s high-density historic districts, and the coverage radius of refuge green space is not applicable. However, many resilient public spaces in historic districts could spontaneously transform into emergency spaces. This study aims to review the research on public space transformation and governance in disaster response to find out what lessons can we derive to improve response to future disaster. The research was divided into three stages: literature screening, data analysis, and literature categorisation. The results show that (1) Most of the existing studies are targeted at pre-planning type of disaster prevention from the top-down perspective, while few summaries of the spontaneous disaster response influencing factors. Some scholars have confirmed the potential of resilient public spaces to respond to disasters, and the spontaneous transformation module has shown positive results, but have not established a multidimensional influence mechanism research structure. (2) The spontaneous spatial response is a process of co-operative intervention by multiple types of participants. The different modes of their co-operation have different outcomes. This review provides useful summaries for the future use of resilience in historic districts in response to disasters, with potential value in finding balanced cooperation across participants.